2007
DOI: 10.1016/s1472-6483(10)60380-x
|View full text |Cite
|
Sign up to set email alerts
|

An economic evaluation of highly purified HMG and recombinant FSH based on a large randomized trial

Abstract: Public funding for IVF is increasingly being challenged by health authorities in an attempt to minimize health service costs. In light of treatment rationing, the need to consider costs in relation to outcomes is paramount. To assess the cost implications of gonadotrophin treatment options, an economic evaluation comparing highly purified human menopausal gonadotrophin (HP-HMG) and recombinant FSH (rFSH) has been conducted. The analysis is based on individual patient data from a large randomized controlled tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
2
17
1
Order By: Relevance
“…For example, NICE guidelines published in 2004 suggest an average IVF cost per cycle of £2771 (6). A recently published assessment of costs based on the MERiT clinical data alone suggested that the costs of HP-hMG and rFSH treatment were £2396 and £2633, respectively (27). In addition, Lloyd et al established that the cost for one IVF cycle was £2423 with HP-hMG and £2745 with rFSH; however, these estimates are based on a combined IVF and ICSI population (26).…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…For example, NICE guidelines published in 2004 suggest an average IVF cost per cycle of £2771 (6). A recently published assessment of costs based on the MERiT clinical data alone suggested that the costs of HP-hMG and rFSH treatment were £2396 and £2633, respectively (27). In addition, Lloyd et al established that the cost for one IVF cycle was £2423 with HP-hMG and £2745 with rFSH; however, these estimates are based on a combined IVF and ICSI population (26).…”
Section: Figurementioning
confidence: 99%
“…HP-hMG alone was compared with rFSH, but the analysis combined IVF and intracytoplasmic sperm injection (ICSI) patients (26). Of all identified economic studies involving HP-hMG, only one was based on patient-level data from a randomized trial (27), and in one, efficacy data were extracted from a meta-analysis (24). While many studies reported cost per clinical or ongoing pregnancy (18,19,(22)(23)(24)(25)(26)28), cost per live birth or per baby was addressed less frequently (29) and mainly in studies not involving comparison of gonadotropins (27).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…An economic analysis is therefore also considered to guide both couples and infertility practitioners. Three articles compared the cost-effectiveness of rFSH versus urinary gonadotropins: Menopur is consistently found to be less expensive than rFSH in terms of mean cost per treatment cycle and/or the cost per ongoing pregnancy [20][21][22] .…”
Section: Discussionmentioning
confidence: 99%